Application of Zeolite-KMnO4 and Silica Gel to Extend Green Life of Manggo Arumanis (Mangifera indica L) - Anita Khairunnisa; Emmy Darmawati; Siti Mariana Widayanti (Jurnal Keteknikan Pertanian, 2021)
Mangoes are harvested when ripe have an "eating quality" that consumers are them in, but quickly reach the senescence phase, making it less profitable for businesses. As a climacteric fruit, the ripening process of mango can be slowed down by using an ethylene adsorber. This study aims to determine the combination of zeolite-KMnO4 and silica gel as ethylene adsorber (EAB) to maintain the green life of ripe The material used is ethylene adsorber (EAB) which is applied to mango arumanis which is packaged with a weight package of 1000±50 g. After the shelf life is reached, the EAB is removed from the packaging and the mangoes are left at room temperature for natural ripening and continued until conditions are not acceptable to consumers. The results showed that the EAB application was able to maintain the green life of mangoes by the scenario of the shelf life both at cold and room temperature storage. Natural ripening of mango was achieved 5 days and 2 days after EAB was removed from the packaging, for cold and room temperature storage, respectively. The length of time until the panellists did not receive it was 20 days for cold storage and 12 days for the room, while the control for cold storage was 6 and 3 days at room temperature